1961
DOI: 10.1042/bj0790193
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositides. 3. Enzymic hydrolysis of inositol-containing phospholipids

Abstract: Sloane-Stanley (1953) and Rodnight (1956) described the hydrolysis of ox-brain 'diphosphoinositide' preparations (Folch, 1949) by extracts of brain and other tissues. Dawson (1954) and Hokin & Hokin (1956) showed that the phosphoinositide fraction of several tissues had a high tumover rate, as measured by the incorporation of 82P. The exact structure of the phosphoinositides involved is not known in every case, but it seems that the phosphate of phosphatidylinositol has a rapid tumover in several tissues (see … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
69
0

Year Published

1965
1965
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(72 citation statements)
references
References 24 publications
(7 reference statements)
3
69
0
Order By: Relevance
“…This non-specific effect of charge is noted by the observation that the extent and rate of increase in surface pressure can be duplicated by other bivalent ions, but the enzyme remain inactive. The fiilure of other bivalent ions to activate the enzyme to any significant extent is a consistent feature of the reaction in dispersed substrates (Atherton & Hawthorne, 1968), and with a number of other preparations, Mg2+ appears to be the best substitute for Ca2+ (Kemp et al, 1961;Thompson, 1967). It should be noted also that EDTA prevents enzyme penetration if all the Ca2+ is cnmpiexed, but fi this instance any specific effects of the cation on the enzyme will also be blocked, The second factor suggesting the binding of Ca2+ to the enzyme was reported by Thompson (1967), who showed that an enzyme purified from rat brain had a certain amount of tightly bound Ca2+ which could not be removed readily by dialysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This non-specific effect of charge is noted by the observation that the extent and rate of increase in surface pressure can be duplicated by other bivalent ions, but the enzyme remain inactive. The fiilure of other bivalent ions to activate the enzyme to any significant extent is a consistent feature of the reaction in dispersed substrates (Atherton & Hawthorne, 1968), and with a number of other preparations, Mg2+ appears to be the best substitute for Ca2+ (Kemp et al, 1961;Thompson, 1967). It should be noted also that EDTA prevents enzyme penetration if all the Ca2+ is cnmpiexed, but fi this instance any specific effects of the cation on the enzyme will also be blocked, The second factor suggesting the binding of Ca2+ to the enzyme was reported by Thompson (1967), who showed that an enzyme purified from rat brain had a certain amount of tightly bound Ca2+ which could not be removed readily by dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction rate was independent of initial surface pressures of less than about 22niN m-but at higher pressures the rate decreased. This decrease could be prevented by the addition of lOmol of octadecylamine/ 90mol of phosphatidylinositol to the substrate monolayer; the amine did not increase the rate of reaction in films of less than 22mN m 1.Phosphatidylinositol phosphodiesterase is an enzyme found widely distributed among various tissues from a number of different species, The enzyme from mammalian tissues cleaves phosphatidylinositol into diacylglycerol and inositol monophosphate (Dawson, 1959;Kemp et al, 1961; Atherton & Hawthome, 1968;Friedel et al, 1969 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This mild solvent fixation avoids any decomposition of inositol 1: 2-cyclic phosphate. WVhen the procedure of Kemp et al (1961) employing trichloroacetic acid was used, complete decomposition of the cyclic phosphate occurred. Paper ionophoresis (Jungalwala et al 1971) of the water-soluble phosphate esters revealed two components, a minor one (MPI 0.70), which migrated to the same position as inositol 1-phosphate (prepared by the procedure of Brown, Hall & Letters, 1959), and an unknown major spot (Mpt 0.76).…”
mentioning
confidence: 99%
“…The enzyme preparation was usually a pig thyroid 0.25M-sucrose supernatant or a partially purified rat liver 'phosphatidylinositol hydrolase' [25-40%-satd.-(NH4)2-S04 fraction; Kemp et al 1961]. After incubation (20-40min) the mixture was shaken with methanol (1.6vol.)…”
mentioning
confidence: 99%